The within-participant Correlation between s-RPE and Heart Rate in Youth Sport - Scantlebury, Sean; Till, Kevin; Atkinson, Greg; Sawczuk, Tom; Jones, Ben (Sports Medicine International Open, 2017)
The monitoring of training load is important to ensure athletes are adapting optimally to a training stimulus. Before quantification of training load can take place, coaches must be confident that the tools available are accurate. We aimed to quantify the within-participant correlation between the session rating of perceived exertion (s-RPE) and summated heart rate zone (sHRz) methods of monitoring internal training load. Training load (s-RPE and heart rate) data were collected for rugby, soccer and field hockey field-based training sessions over a 14-week in-season period. A total of 397 sessions were monitored (rugby n=170, soccer n=114 and field hockey n=113). Within-subject correlations between s-RPE and sHRz were quantified for each sport using a general linear model. Large correlations between s-RPE and the sHRz method were found for rugby (r=0.68; 95% CI 0.59–0.75) and field hockey (r=0.60; 95% CI 0.47–0.71) with a very large correlation found for soccer (r=0.72; 95% CI 0.62–0.80). No significant differences were found between the correlations for each sport. The very large and large correlations found between s-RPE and the sHRz methods support the use of s-RPE in quantifying internal training load in youth sport.
Keywords: training load; periodisation; soccer; rugby; hockey